Direct Synthesis of 1-Alkyl-6-hydroxyalkyl-3a,6a-diphenylglycolurils from 1-Alkylimidazolinones and Their Cyclic Analogues - Baranov, Vladimir V.; Antonova, Maria M.; Kolotyrkina, Natalya G.; Zanin, Igor E.; Kravchenko, Angelina N. (Synlett, 2019)
Two methods for the direct synthesis of previously inaccessible 1-alkyl-6-(hydroxyalkyl)-3a,6a-diphenylglycolurils have been developed as a result of a study of novel cyclocondensations of 1-alkylureas with tetrahydroimidazooxazolones, tetrahydroimidazooxazinones and 1-(hydroxyalkyl)ureas with 1-substituted imidazolinones. A mechanism to rationalize the highly regioselective formation of the target glycolurils is proposed.
Keywords: glycolurils; imidazolinones; condensation